2019
DOI: 10.1242/bio.041467
|View full text |Cite
|
Sign up to set email alerts
|

Detection of changes in mitochondrial hydrogen sulfide i n vivo in the fish model Poecilia mexicana (Poeciliidae)

Abstract: In this paper, we outline the use of a mitochondria-targeted ratiometric mass spectrometry probe, MitoA, to detect in vivo changes in mitochondrial hydrogen sulfide (H 2 S) in Poecilia mexicana (family Poeciliidae). MitoA is introduced via intraperitoneal injection into the animal and is taken up by mitochondria, where it reacts with H 2 S to form the product MitoN. The MitoN/MitoA ratio can be used to assess relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Inside mitochondria, MitoA reacts with H 2 S and is converted to MitoN. The ratio of MitoN/MitoA can be quantified using liquid chromatography with tandem mass spectrometry and serve as a metric of mitochondrial H 2 S. We used a MitoA protocol specifically validated for P. mexicana (39). Fish injected with MitoA were exposed to different environmental H 2 S concentrations for 5 h. Gill, liver, brain, and muscle tissues were sampled from fish and used for the quantification of MitoN/MitoA ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Inside mitochondria, MitoA reacts with H 2 S and is converted to MitoN. The ratio of MitoN/MitoA can be quantified using liquid chromatography with tandem mass spectrometry and serve as a metric of mitochondrial H 2 S. We used a MitoA protocol specifically validated for P. mexicana (39). Fish injected with MitoA were exposed to different environmental H 2 S concentrations for 5 h. Gill, liver, brain, and muscle tissues were sampled from fish and used for the quantification of MitoN/MitoA ratios.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it will also be interesting to investigate precisely how H 2 S production varies in different tissues and in different cellular locations following DR. These approaches may be made more feasible with the advent of novel chemical probes to determine H 2 S in vivo (Arndt et al 2017;Lau et al 2019). However, irrespective of these caveats, we have shown that endogenous H 2 S levels and associated signalling pathways differ significantly depending on genetic background in mice under both AL and DR conditions.…”
Section: Got1mentioning
confidence: 88%
“…ABSTRACTFirst Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Gigi Lau and Nick Barts are co-first authors on ‘ Detection of changes in mitochondrial hydrogen sulfide in vivo in the fish model Poecilia mexicana (Poeciliidae)’, published in BiO. Gigi is a post-doctoral fellow in the lab of Dr Sjannie Lefevre at the University of Oslo, Norway, adaptive variation in mitochondrial function.…”
mentioning
confidence: 99%